2019
DOI: 10.19184/ams.v5i2.9651
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cholinesterase Levels to Lung Function in Farmer Exposed by Organophosphate Pesticides in Sukorambi Village, Jember Regency

Abstract: AbstrakPenduduk Indonesia mayoritas bermata pencaharian sebagai petani. Aktivitas pertanian memerlukan pestisida untuk memberantas hama dan penyakit tanaman. Pestisida dapat menimbulkan keracunan. WHO menyebutkan terdapat 1-5 juta kasus keracunan pestisida di negara berkembang. Kasus keracunan pestisida di Indonesia sebesar 771 kasus. Pestisida organofosfat masuk ke tubuh melalui inhalasi. Organofosfat bekerja sistemik menghambat enzim kolinesterase menyebabkan gangguan faal paru. Tujuan dari penelitian ini ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The use of personal protective equipment (PPE), personal hygiene, and spraying time were found to be factors in the prevalence of acute pesticide poisoning or health problems such as excessive fatigue, excessive salivation, hard breathing, frequent urination, blurred vision, dizziness, and finger pain, according to research by Joko et al (10) on onion farming workers in the Central Java Province of Indonesia. Similar information was obtained from the Sandra et al (11) study findings, which showed a relationship between lung function and acetylcholinesterase levels in the blood of farmers exposed to chronic organophosphate exposure; the lower the level of acetylcholinesterase, the lower the lung function. Pesticides are also known to cause multiple myeloma, sarcoma, prostate and pancreatic cancer, uterine, pancreatic, and Hodgkin's diseases, among other health issues (12)(13)(14).…”
Section: Introductionsupporting
confidence: 82%
“…The use of personal protective equipment (PPE), personal hygiene, and spraying time were found to be factors in the prevalence of acute pesticide poisoning or health problems such as excessive fatigue, excessive salivation, hard breathing, frequent urination, blurred vision, dizziness, and finger pain, according to research by Joko et al (10) on onion farming workers in the Central Java Province of Indonesia. Similar information was obtained from the Sandra et al (11) study findings, which showed a relationship between lung function and acetylcholinesterase levels in the blood of farmers exposed to chronic organophosphate exposure; the lower the level of acetylcholinesterase, the lower the lung function. Pesticides are also known to cause multiple myeloma, sarcoma, prostate and pancreatic cancer, uterine, pancreatic, and Hodgkin's diseases, among other health issues (12)(13)(14).…”
Section: Introductionsupporting
confidence: 82%
“…If the farmer's cholinesterase enzyme levels, normal cholinesterase levels in men are 4620-11500 U/L, while in women they are 3930-10800 U/L. Cholinesterase levels are interpreted as intoxication if cholinesterase activity in the blood decreases by more than 50% of normal or 3500 U/L (13).…”
Section: Cite This Asmentioning
confidence: 99%
“…Cholinesterase levels are used as a marker of pesticide exposure (13). Normal values of cholinesterase for women were 3999-10800 U/L and for men 4620-11500 U/L.…”
Section: Cholinesteration Levelsmentioning
confidence: 99%
See 1 more Smart Citation